Balance perturbations as a measurement tool for trunk impairment in cross-country sit skiing - Rosso, V.; Gastaldi, L.; Rapp, W.; Lindinger, S.; Vanlandewijck, Y.; Äyrämö, S.; Linnamo, V. (Adapted Physical Activity Quarterly, 2023)
In cross-country sit-skiing, the trunk plays a crucial role in propulsion generation and balance maintenance. Trunk stability is evaluated by automatic responses to unpredictable perturbations; however, electromyography is challenging. The aim of this study was to identify a measure to group sit-skiers according to their ability to control the trunk. Seated in their competitive sit-ski, 10 male and 5 female Paralympic sit-skiers received 6 forward and 6 backward unpredictable perturbations in random order. k-means clustered trunk position at rest, delay to invert the trunk motion, and trunk range of motion significantly into 2 groups. In conclusion, unpredictable perturbations might quantify trunk impairment and may become an important tool in the development of an evidence-based classification system for cross-country sit-skiers.